PEMANFAATAN TEKNOLOGI DIGITAL SEBAGAI SARANA USAHA PENGEMBANGAN OBJEK DAN DAYA TARIK WISATA TERHADAP KUNJUNGAN WISATAWAN KE TAMAN WISATA SITINJO KABUPATEN DAIRI - Dameria Girsang; Angelia Septiani Sianga (Jurnal Ilmiah Akomodasi Agung, 2019)
The use of digital technology is expected to help the Dairi Regency Culture and Tourism Office develop and build Objects and Attractions of the Sitmano Iman Tourism Park and how businesses attract tourists through Digital utilization so that tourist attractions are visited and know the obstacles that exist. The analytical method used is field research to find out the problem directly from the field as well as conducting library research by reading books related to research and conducting interviews both with visitors, staff and employees of the Dairi Regency Culture and Tourism Office. From the research carried out that the local government has begun to develop using Digital Information & Technology but it has not been maximized and improvements to existing objects and facilities are proven by the addition of tourist facilities and attractions and it is hoped that the government can place competent human resources to manage these attractions in meaning the government positions competent and quality human resources and cooperates with travel and other private parties in addition to the use of Digital Information Technology so that the Faith Tourism Park can be well promoted and bring in more tourists.